Argumentação probatória e seus reflexos na busca de uma decisão justa no processo penal - Oliveira, Cláudia Caroline Gracioli de (2024)
This paper aims to analyze the importance of probative arguments in criminal proceedings, with the intention of highlighting that, despite the current valuation system being that of free motivated conviction, it is necessary to observe other types of goals that judges and jurors are bound by making a decision. In this vein, emphasis is given to the role of evidentiary standards, a subject that has gained relevance in Brazil in recent years, despite being commonly used in common law countries for some time, bringing to the debate the importance that, in order to convict someone, a judge is necessary. robust, coherent and credible evidence set with the narrated facts. Therefore, the work was divided into four chapters. Thus, the opening chapter brings some introductory notions to the topic addressed, such as the concept, object and purpose of proof, the valuation systems found in the past and the current one, in addition to unraveling the truth in terms of formal truth and real truth. – which for many years was believed to be the aim of criminal proceedings. The second chapter will delve into legal epistemology, along with the construction of a probative reasoning from the different inferences to be analyzed. In turn, the third chapter is dedicated to the study of evidentiary standards of proof, passing through the various institutes, with emphasis on the standard of proof beyond a reasonable doubt, which is applicable and more similar to the high level of validation of the evidentiary framework aimed at the process. criminal. In this way, we will deepen on the difficulty of conceptualizing it, its historical development, its close correlation with the principle of the presumption of innocence and, finally, some criticisms will be pointed out in relation to the referred standard. The last chapter discusses how the evidentiary arguments and their consequent goals are applied by the Superior Courts so that the constitutional precept of due process of law is enforced and, in case of doubt, choose the acquittal of the defendant instead of opting for a wrongful conviction.